Performance Results of a Solar Adsorption Cooling and Heating Unit - Tryfon C. Roumpedakis; Salvatore Vasta; Alessio Sapienza; George Kallis; Sotirios Karellas; Ursula Wittstadt; Mirko Tanne; Niels Harborth; Uwe Sonnenfeld (Energies, 2020)
The high environmental impact of conventional methods of cooling and heating increased the need for renewable energy deployment for covering thermal loads. Toward that direction, the proposed system aims at offering an efficient solar powered alternative, coupling a zeolite–water adsorption chiller with a conventional vapor compression cycle. The system is designed to operate under intermittent heat supply of low-temperature solar thermal energy (<90 °C) provided by evacuated tube collectors. A prototype was developed and tested in cooling mode operation. The results from the testing of separate components showed that the adsorption chiller was operating efficiently, achieving a maximum coefficient of performance (COP) of 0.65. With respect to the combined performance of the system, evaluated on a typical week of summer in Athens, the maximum reported COP was approximately 0.575, mainly due to the lower driving temperatures with a range of 75 °C. The corresponding mean energy efficiency ratio (EER) obtained was 5.8.